PENGEMBANGAN MEDIA PEMBELAJARAN BLOCK QUADRATE PADA MATERI PERSAMAAN KUADRAT DI SMP KELAS IX - Bapa, Agustinus Tamo; Qohar, Abd (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2024)
Learning math in junior high school often feels difficult or hard for students. One of the efforts that can be made to avoid difficulties experienced by students is to use appropriate and interesting learning media. This research aims to develop Block Quadrate manipulative learning media in mathematics subjects in junior high school / middle school, especially in the material of quadratic equations. This research was developed with the steps of the modified Borg & Gall model. Data collection techniques and data analysis are tested on a small / limited scale or large scale. The procedure in the research is to analyze the product being developed, product validation, and product trials. The test subjects in this study were 17 D2-Magister of Mathematics Education students on quadratic equation material. The results of the validity analysis showed that the media met the valid criteria with an average score of 3.46. The practicality analysis results show that the media is practical with an average score of 3.53. Based on the results of the analysis, the use of this learning media is highly recommended for quadratic equation material.